Exogenous and endogenous lipids of human hair. Issue 4 (13th March 2017) - Coderch, L.; Oliver, M. A.; Martínez, V.; Manich, A. M.; Rubio, L.; Martí, M.
Abstract : Purpose: The aim of this study was to characterize the external and internal lipids of Caucasian hair and their influence in different hair properties such as moisture content, hydrophobic character, and mechanical properties. Methods: Lipid extraction and their analysis by thin layer chromatography with flame ionization detector were carried out. Lipid rearrangement and water sorption and desorption evaluation of these fibers with and without lipids will also be determined using different techniques such as differential scanning calorimetry, thermogravimetric analysis and dynamic vapor sorption, mainly to evaluate permeation changes of these hair fibers possibly related to the fluidity of the lipids extracted. Results: Caucasian fibers were found to be well hydrated, and moisture diminution was observed mainly for the external lipid extracted fibers. Unexpectedly, the lipid extraction promoted an increase in the break tenacity of the Caucasian fibers. The hydrophobic character of the fiber surfaces indicates the marked hydrophobicity of all fibers. Delipidization promotes only a slight diminution of their hydrophobic properties. Water uptake and desorption studies indicate an important water regain for Caucasian fibers. The external extracted hair fibers presented a diminution of maximum water regain, which surprisingly increases with the following internal lipid extraction. This can be due to a higher water desorption found only for external extracted fibers. Conclusions: The relationship between fluidity of lipids extracted and hair fiber water diffusion were established. Extraction of internal lipids of Caucasian fibers, which have a higher unsaturated lipid content than external lipids of the same hair fiber, leads to a lower water permeability of the fiber. On the capillar formulations should be considered the importance of lipid fluidity to modify the permeability of the fiber.